Evolution of trauma care and the trauma registry in the West Australian health system - Mayura Thilanka Iddagoda; Maxine Burrell; Sudhakar Rao; Leon Flicker (Journal of Trauma and Injury)
Trauma care is evolving throughout the world to meet the demand resulting from rapidly increasing rates of mortality and morbidity related to external injuries. The State Major Trauma Service was designated to Royal Perth Hospital in 2004 to provide comprehensive care for trauma patients in Western Australia (WA), which is the largest state by area in the country. The State Major Trauma Unit, which was established in 2008, functions as a level I center and admits over 1,000 major trauma patients per year, making it the second busiest trauma center in Australia. The importance of recording data related to trauma was identified by the trauma service in WA to inspire higher standards of patient care and injury prevention. In 1994, the service established a trauma registry, which has undergone significant changes over the last two decades. The current State Trauma Registry is linked to a statewide database called the Data Linkage System. The linked data are available for policy development, quality assurance, and research. This article discusses the evolution of the trauma service and the registry database in the WA health system. The State Trauma Registry has enormous potential to contribute to research and quality improvement studies along with its ability to link with other databases.